Pengaruh Aplikasi TikTok sebagai Media Dakwah terhadap Mahasiswa Manajemen Dakwah Universitas Islam Negeri Sumatera Utara - Efendi, Erwan; Asmar, Dailami; Fazar , Taufiq (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The aim of this research is to map TikTok behavior as a marketing strategy. The main group of this research are students of Da'wah Management, Faculty of Da'wah and Communication, North Sumatra State Islamic University. This type of research is qualitative and descriptive research. Research tools include observation, structured questions (interview guide) and interviewers as the main tools. The source of information for this research comes from interviews with Da'wah Management students. The results of this research show that Da'wah Management students who use the social media platform TikTok use this form of communication as a means to increase their knowledge, learn about Da'wah and teach the Islamic religion, as well as encourage them to do good deeds. In fact, they can easily get information about da'wah through this application. That's normal. On the other hand, their communication style is also decent if they are harmless and good at organizing informational videos and general promotions